From Posts to Purchases: Insights into the Influence of Social Media's Influencers on Retail Consumers’ Purchase Intention - Mya, Chanel Chai Ker Er; Bhardwaj, Rajeev; Krishnasamy, Hariharan N; Albakri, Ramzia; Senathirajah, Abdul Rahman Bin S; Haque, Rasheedul (Journal of Posthumanism, 2025)
This study aims to investigate how customer purchase intentions among Malaysian internet shoppers are influenced by social media influencers, where attributes of influencers were investigated. Previous studies on social media marketing, influencer attributes, and consumer behaviour served as the foundation for the conceptual model. Likeability, trustworthiness of the influencer, attractiveness, and influencer expertise are the key variables. This study utilized the Elaboration Likelihood Model (ELM) and the Source Credibility Theory as the underlying theories. Following a thorough analysis of relevant research, a structured questionnaire was created, and 142 respondents' responses was gathered using purposive sampling. To determine whether the suggested research model was significant, multiple regression analysis was used. The results show that the influencer’s expertise had a significant impact on consumers' intention to make purchases. However, influencer’s trustworthiness, likeability, and attractiveness were non-significant factors. By concentrating on these important elements, marketers and businesses can improve their social media strategy by applying the implications of this study. This study's primary contribution was towards understanding the impact of social media influencers on purchase intentions in on the pharmaceutical industry within the Malaysian context.